2018
DOI: 10.3390/su11010091
|View full text |Cite
|
Sign up to set email alerts
|

Research on Resource Curse Effect of Resource-Dependent Cities: Case Study of Qingyang, Jinchang and Baiyin in China

Abstract: For a specific small-scale region with abundant resources, its copious resources tend to dictate the basic direction of its development, and may subsequently give rise to an industrial structure centered on the advantageous resources. This can give rise to an economic structure that lacks diversity, causing the economic development in the entire local region to fall into the dilemma of the resource curse. The present study conducts a case study from the perspective of small-scale regions, incorporating various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Combining expert opinions with the relevant references [29,30,31,32,33], the specific index calculation methods are shown in Table 5.…”
Section: Methodsmentioning
confidence: 99%
“…Combining expert opinions with the relevant references [29,30,31,32,33], the specific index calculation methods are shown in Table 5.…”
Section: Methodsmentioning
confidence: 99%
“…In China, many empirical studies have been carried out at the national and provincial levels [37]. For example, Xu and Wang [38] selected raw coal, crude oil, and pig iron as representatives of natural resources to study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, the research objects are mostly concentrated on coal, oil, gold, and other traditional natural resources. Second, the research areas are mostly focused on the macro-level [37,39]. However, the larger spatial scale is easy to ignore the smaller regional category's spatial heterogeneity, thus covering up the role of resource abundance on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang and Brouwer [17] analyzed 44 studies published in Chinese between 2005 and 2017, and found that the existence of the resource curse was ambiguous in China. Lu et al [6] found that the resource curse effect is strongest for a resource-dependent city during an economic recession, less severe during a development period, and weakest during maturation with a case study of Qingyang, Jinchang, and Baiyin in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have tested the theory of the resource curse. However, scholars have not taken resource price fluctuations into consideration [1][2][3][4][5][6], with the exception of Douglas and Walker [7]. Actually, in resource-rich areas, the resource industry makes up a large portion of the national economy, and resource price fluctuations exert a greater influence on local economic growth.…”
Section: Introductionmentioning
confidence: 99%